Irritable Bowel Syndrome and Psychiatric Disorders in Pakistan: A Case Control Study. (28th February 2012) - Butt, Amna Subhan; Salih, Mohammad; Jafri, Wasim; Yakoob, Javed; Wasay, Mohammad; Hamid, Saeed
Abstract : Background . The psychiatric disorders like anxiety and depression could have a profound influence on onset, expression, and course of Irritable bowel syndrome (IBS). Aim . To estimate the frequency and strength of association of common mental disorders (CMDs) in patients with IBS and patients with other chronic diseases, that is, migraine and hypertension. Method . This was a case control study. Individuals aged 18–70 years diagnosed as IBS were enrolled as cases. The control groups consisted of patients without IBS but diagnosed to have a chronic disease, that is, migraine or HTN. Self-Reporting Questonnaire-20(SRQ-20) was used as a screening tool for the detection of CMD. Results . 82 patients were enrolled in each group. Mean SRQ score was significantly higher in IBS group than controls (9.9 ± 4.5 versus 4.9 ± 3.6, P < 0.001 ). CMDs were more frequent (67.1% versus 22%) and the odds of CMD were 7.24 times higher among IBS patients than controls (95% CI 3.6–14.5, P < 0.001 ). No difference was found in frequency of CMDs among various subtypes of IBS. Conclusion . We found that CMDs are more common and strongly associated with IBS as compared to other chronic diseases. Early screening for CMDs might be useful for an effective management of IBS.